2015
DOI: 10.1111/hir.12119
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge for Healthcare: the future of health librarianship

Abstract: Many people are still not receiving the right care. It is imperative for health care librarians to come together around a common vision to achieve Knowledge for Healthcare so that the right knowledge and evidence is used at the right time in the right place. The authors describe five workstreams within a modernisation programme: Service Transformation, Workforce Planning and Development, Quality and Impact, Resource Discovery and Optimising Investment. Communications, engagement and partnership working are cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They indicated that health sciences librarians have lots of ideas but the real challenge is to find the right managers and administrators who are willing to see a larger picture for librarians' engagement in the research, clinical and educational enterprise of their institution. Bryant et al (2015) observed that health information consumers are not receiving the right information. They are ignorant about the role librarians perform, and their importance in health care knowledge delivery in the system is obscure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They indicated that health sciences librarians have lots of ideas but the real challenge is to find the right managers and administrators who are willing to see a larger picture for librarians' engagement in the research, clinical and educational enterprise of their institution. Bryant et al (2015) observed that health information consumers are not receiving the right information. They are ignorant about the role librarians perform, and their importance in health care knowledge delivery in the system is obscure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several organizations have become involved in digital transformation by adopting various educational strategies (OECD, 2022;UNESCO, 2019). The European health committee has recommended a more significant emphasis on training health professionals for the future of care and transformation towards digital health in clinically directed practices, teaching, and research (Bryant et al, 2015). The continuing education of health professionals faces significant challenges in the knowledge society and e-Health.…”
Section: Introductionmentioning
confidence: 99%